2022
DOI: 10.25259/cytojournal_49_2021
|View full text |Cite
|
Sign up to set email alerts
|

Application of the international system for reporting serous fluid cytopathology on reporting various body fluids; experience of a tertiary care hospital

Abstract: Objectives: Cytological examination of effusion sample is a preliminary and minimally invasive method for the diagnosis of body fluids. Recently, the International System For Reporting Serous Fluid Cytopathology (ISRSFC) and the Indian Academy of Cytologist (IAC) have published guidelines for reporting effusion cytology and calculating the risks of malignancy (ROMs) for each defined category. We report our 2 years of experience in reclassifying and assessing the feasibility of applying ISRFSC and IAC categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Evaluation of pericardial effusions has been reported in 10 studies, five of which reported ROM assessments (Table 1). [20][21][22][23][24][25][26][27][28][29] The number of samples/patients in studies with reported ROM ranged from 64 to 574. The estimated ROM for each category was: ND, 0%-100%; NFM, 1.3%-17.4%; AUS, 0%-35%; SFM, 57.1%-100%; MAL, 89.3%-100%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evaluation of pericardial effusions has been reported in 10 studies, five of which reported ROM assessments (Table 1). [20][21][22][23][24][25][26][27][28][29] The number of samples/patients in studies with reported ROM ranged from 64 to 574. The estimated ROM for each category was: ND, 0%-100%; NFM, 1.3%-17.4%; AUS, 0%-35%; SFM, 57.1%-100%; MAL, 89.3%-100%.…”
Section: Discussionmentioning
confidence: 99%
“…There were 13 studies that included pleural effusions, 10 of which reported ROM evaluation (Table 2). 18,[20][21][22][24][25][26][29][30][31][32][33][34] The number of samples/patients ranged from 350 to 2454. The estimated ROM for each category was: ND, 0%-57.1%; NFM, Eleven studies provide data for peritoneal effusions, and ROM was assessed in seven of them (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations